Early Makuria Research Project El-Zuma Cemetery - Czyżewska-Zalewska, Ewa (Harvard Egyptological studies,, 2021)
"The three-volume publication of the results of archaeological excavations at the UNESCO heritage site of El-Zuma in Sudan, investigated by PCMA University of Warsaw and the National Corporation for Antiquities and Museums in Khartoum, presents an Early Makurian elite tumuli cemetery from the 5th-6th centuries C.E. This period in ancient Nubian history, preceding the rise of the Christian kingdoms, has long been understudied. Informed analyses by an array of specialists on the team cover the archaeological and bioarchaeological evidence from the tombs (Volume I) as well as the abundant ceramics (Volume II) and small finds, especially jewellery, weaponry and personal accessories (Volume III). The outcome is a people-oriented view of an elite community in ancient Nubia at the dawn of a new age in its history"--